Effect of protective lung ventilation on pulmonary complications after laparoscopic surgery: a meta-analysis of randomized controlled trials - Sun, Menglin; Jia, Ruolin; Wang, Lijuan; Sun, Daqi; Wei, Mingqian; Wang, Tao; Jiang, Lihua; Wang, Yuxia; Yang, Bo (Frontiers in Medicine, 2023)
Introduction Compared with traditional open surgery, laparoscopic surgery is widely used in surgery, with the advantages of being minimally invasive, having good cosmetic effects, and having short hospital stays, but in laparoscopic surgery, pneumoperitoneum and the Trendelenburg position can cause complications, such as atelectasis. Recently, several studies have shown that protective lung ventilation strategies are protective for abdominal surgery, reducing the incidence of postoperative pulmonary complications (PPCs). Ventilator-associated lung injury can be reduced by protective lung ventilation, which includes microtidal volume (4–8 mL/kg) ventilation and positive end-expiratory pressure (PEEP). Therefore, we used randomized, controlled trials (RCTs) to assess the results on this topic, and RCTs were used for meta-analysis to further evaluate the effect of protective lung ventilation on pulmonary complications in patients undergoing laparoscopic surgery. Methods In this meta-analysis, we searched the relevant literature contained in six major databases—CNKI, CBM, Wanfang Medical, Cochrane, PubMed, and Web of Science—from their inception to October 15, 2022. After screening the eligible literature, a randomized, controlled method was used to compare the occurrence of postoperative pulmonary complications when a protective lung ventilation strategy and conventional lung ventilation strategy were applied to laparoscopic surgery. After statistical analysis, the results were verified to be statistically significant. Results Twenty-three trials were included. Patients receiving protective lung ventilation were 1.17 times less likely to develop pulmonary complications after surgery than those receiving conventional lung ventilation (hazard ratio [RR] 0.18, 95% confidence interval [CI] 1.13–1.22; I2 = 0%). When tested for bias (P = 0.36), the result was statistically significant. Patients with protective lung ventilation were less likely to develop pulmonary complications after laparoscopic surgery. Conclusion Compared with conventional mechanical ventilation, protective lung ventilation reduces the incidence of postoperative pulmonary complications. For patients undergoing laparoscopic surgery, we suggest the use of protective lung ventilation, which is effective in reducing the incidence of lung injury and pulmonary infection. Implementation of a low tidal volume plus moderate positive end-expiratory pressure strategy reduces the risk of postoperative pulmonary complications.